2017
DOI: 10.1021/jacs.6b11354
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Hexamethyldisilazide-Mediated Enolization of Acylated Oxazolidinones: Solvent, Cosolvent, and Isotope Effects on Competing Monomer- and Dimer-Based Pathways

Abstract: Lithium hexamethyldisilazide (LiHMDS)-mediated enolization of (+)-4-benzyl-3-propionyl-2-oxazolidinone in THF–hydrocarbon mixtures shows unusual sensitivity to the choice of hydrocarbon cosolvent (hexane versus toluene) and to isotopic labeling. Four mechanisms corresponding to monosolvated monomers, trisolvated dimers, octasolvated monomers, and octasolvated dimers were identified. Even under conditions in which the LiHMDS monomer was the dominant observable form, dimer-based metalation was significant. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 114 publications
0
18
0
Order By: Relevance
“…Of course, 2:2 mixed tetramer ( S )- 15a is necessarily unsolvated in toluene, 28 and studies with THF suggested that ( S )- 15a does not accept coordinating solvents either. Using a control experiment of increasing importance in our laboratory, we added pyridine to toluene solutions to probe lithium ion solvation.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, 2:2 mixed tetramer ( S )- 15a is necessarily unsolvated in toluene, 28 and studies with THF suggested that ( S )- 15a does not accept coordinating solvents either. Using a control experiment of increasing importance in our laboratory, we added pyridine to toluene solutions to probe lithium ion solvation.…”
Section: Resultsmentioning
confidence: 99%
“…If the reaction had proceeded via a single mechanism involving disolvated monomer (AS 2 ), such as transition structure 5 , a maximum in the plot at intermediate THF concentrations would have been observed. 20 That the rates continue rising even as trisolvated monomer becomes dominant demands that an even more highly solvated form be involved in the enolization. By monitoring the THF-dependent E/Z selectivities over the analogous range of THF concentrations, we separated the components of the two pathways and showed that they contribute to second- and third-order dependencies (see Figure 4, curves A and B, respectively).…”
Section: Enolate Structures: Thfmentioning
confidence: 99%
“…Using toluene in place of hexane resulted in no measurable difference in the THF dependence, which seems self-evident except that pronounced hydrocarbon effects on LiHMDS/THF-mediated enolizations have been observed. 20 …”
Section: Enolate Structures: Thfmentioning
confidence: 99%
“…Only recently did we begin to address the challenges of the influence of multiple reactants on observable rate behavior. 29 …”
Section: Discussionmentioning
confidence: 99%
“…If, for example, “AS” is the reactive form, driving the reactant to AS 2 by using a high solvent concentration will inhibit the metalation. 29 12normalA2normalS22em↽2em ⇀ Keq[AS]2em ↽ 2em⇀Keq[normalS]AS2…”
Section: Discussionmentioning
confidence: 99%